Procesos de planificación y la ejecución presupuestaria en función de la misión y visión de la Universidad Técnica de Babahoyo en el periodo 2018 - Hurtado Romero, Marcos Jeampol (2020)
The present case study has been carried out with the conditions of analyzing the level and compliance of the budget execution at 100% of the institutional planning based on the mission and vision of the Technical University of Babahoyo taking into account the administration and control of the processes directing towards the objectives and goals, where an incomplete execution of the expense reports was determined, the fiscal resources must be managed and controlled with a vision approach to the application of programs and projects managed with efficiency, effectiveness, effectiveness , improving the quality in the institutional axes.